2021
DOI: 10.3389/fpsyg.2021.678188
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Threat and In-group Cooperation

Abstract: Disease-causing parasites and pathogens play a pivotal role in intergroup behavior. Previous studies have suggested that the selection pressure posed by pathogen threat has resulted in in-group assortative sociality, including xenophobia and in-group favoritism. While the current literature has collated numerous studies on the former, strikingly, there has not been much research on the relationship between pathogen threat and in-group cooperation. Drawing upon prior studies on the function of the behavioral im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Once formed, these two kinds of relations can exist simultaneously in a cultural system, and their proportion in the group, the strength of relationship construction, and the extension of relations will profoundly affect the development of culture. diseases at the collective level (Imada & Mifune, 2021). The effectiveness of cooperation among individuals has been demonstrated in previous research on avian flu (Ferguson et al, 2005).…”
Section: Immune Systemmentioning
confidence: 74%
See 1 more Smart Citation
“…Once formed, these two kinds of relations can exist simultaneously in a cultural system, and their proportion in the group, the strength of relationship construction, and the extension of relations will profoundly affect the development of culture. diseases at the collective level (Imada & Mifune, 2021). The effectiveness of cooperation among individuals has been demonstrated in previous research on avian flu (Ferguson et al, 2005).…”
Section: Immune Systemmentioning
confidence: 74%
“…Activation of the behavioral immune system requires cues related to pathogen information, while activation of the collective-level behavioral immune system will increase the intensity of social norms and the frequency of healthy behaviors within groups, reducing the risk of infection caused by intragroup violations (Morsky et al, 2022;Szekely et al, 2021). In addition, activation of the group behavioral immune system can also promote cooperative behavior and provide social support to individuals (Imada & Mifune, 2021). Implementation of public health measures also helps reduce the public's perception of health risks, which is closely related to group health anxiety (Malhotra et al, 2020;Mohd Salleh Sahimi et al, 2021;Renner et al, 2008).…”
Section: Immune Systemmentioning
confidence: 99%
“…Our meta-analyses, overall, provided little evidence that COVID-19 threat is meaningfully associated with in-group attitudes. Imada and Mifune (2021) suggested that fear of contracting a disease might not necessarily be relevant to in-group attitudes. They argue that pathogen stress had shaped in-group-oriented attitudes because this would help individuals acquire social support when they are sick and in need of support.…”
Section: Discussionmentioning
confidence: 99%
“…Fincher and Thornhill (2012) argued that the BIS triggers behavioral avoidance toward others living outside of their natal area (i.e., out-group members) but also behavioral approach toward in-group members, and several studies have collated supporting evidence (e.g., Laakasuo et al, 2018; Navarrete & Fessler, 2006). First, studies show that the BIS is associated with in-group-oriented feelings and behaviors, such as increased positive in-group attitudes, conformity, and collectivism (see Imada & Mifune, 2021). Second, evidence suggests that the more sensitive individuals are to pathogens, the more negative their attitudes toward out-group members—especially immigrants (Aaroe et al, 2017; Faulkner et al, 2004; Hodson et al, 2013; Ji et al, 2019; Karinen et al, 2019; Kim et al, 2016).…”
Section: Bis and Intergroup Attitudesmentioning
confidence: 99%
“…Increased linguistic distance could promote avoidance of those that may be associated with a higher risk of infection. Similarly, a concomitant decrease in the perceived linguistic distance between participants and ingroup members may facilitate affiliative and approach‐related behaviors aimed at garnering sources of support if actual infections were to occur (Imada & Mifune, 2021 ). This is consistent with research that found that injection with an immune stimulant (lipopolysaccharide) elicited increased desire to spend time with support figures (Inagaki et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%